LEARNING MANAGEMENT OF ISLAMIC EDUCATION AT SDN 3 KERENG BANGKIREI PALANGKARAYA - Jasiah Jasiah (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2018)
The aim of this research was to describe the learning management of Islamic Education at SDN 3 Kereng Bangkirei Palangkaraya. This research used a qualitative approach. The subject of research were the teacher of Islamic education class III at SDN 3 Kereng Bangkirei Palangkaraya, while the informants were the principal, the classroom teacher, and several students of class III at SDN 3 Kereng Bangkirei Palangkaraya. Data collection techniques used were interviews, observation, and documentation. Data validation was carried out by means of triangulation. Data analysis consists of four stages, namely data collection, data reduction, data presentation, and conclusion or verification. The research result showed that: 1) The learning management of Islamic Education, starting from the implementation of pre-activity, the delivery of materials, the use of methods, the use of media, and the implementation of post-activity, was conducted well. Its implementation was also in accordance with what had been formulated in the lesson plan. 2) The factors supporting the learning implementation of Islamic education at SDN 3 Kereng Bangkirei Palangkaraya were the availability of classrooms with desks and chairs for teacher and students, teacher’s handbook, and textbooks which could be borrowed by students, while the factors inhibiting the learning implementation of Islamic education at SDN 3 Kereng Bangkirei Palangkaraya were the unavailability of the worship space and the lack of tools or learning media.